Immunotherapy for Atherosclerosis - Monaco, Claudia; McNamara, Coleen A.; Slütter, Bram; Foks, Amanda C.; Bekiranov, Stefan; Mulder, Willem J.M.; Mulder, Willem J.M.; Goncalves, Isabel ; 0000-0002-2935-0181; Lutgens, Esther (Physiological Reviews, 2025)
Cardiovascular disease is the global number one causeof mortality and morbidity. The majority of cardio vascular diseases are caused by atherosclerosis, a lipid-driven, inflammatory disease of the middle- and large-sized arteries. The disease is characterized by the formation of atherosclerotic plaques throughout the arterial tree. Over the years, insights intohe pathogenesis of atherosclerosis have shifted from a “lipid-driven” model to a “response-to-injury” perspective and more recently to a “lipid-driven inflammatory disease” viewpoint.We are now aware that a network of multiple immune cell types andsubsets of the innate and adaptive immune system inhabit our arteries. Intricate interactions between these immune cell subsets, nonimmune cells, and local environmental substances such as lipids, cell debris, and calcium cause a fluidic balance ofproinflammatory and regulatory responses. A dysregulationof this balance toward a proinflammatory milieu drives atherosclerotic disease progression. Although we have acknowl edged that atherosclerosis is an inflammatory disease, state-of-the-art treatments are still based on lipid lowering, antihypertensive, and lifestyle-changing strategies. In the past decade, clinical phase I, II, and III trials targeting the immune systemrevealed that patients tolerate immunotherapy, show decreased inflam mation, and/or have a reduction in cardiovascular endpoints.However, the search for novel immunothera peutic targetsand treatment regimens as well as stratification of patients who would benefit fromsuch treatments to combat atheroscleroticcardiovascular disease is only just beginning. In this review article, we will highlight the newest insights on the different cellsubsets and components of the immune system in atherosclerosisand elaborate on current and future immunotherapeuticsto treatatherosclerotic cardio vascular disease.
Publisher Copyright: © 2025 the American Physiological Society.
Keywords: atherosclerosis; cardiovascular disease; immunology; immunotherapy; inflammation